A study on clinical profile, complications and outcome of scrub typhus in south Indian children - Balaji, J.; Punitha, P.; Ramesh Babu, B.; Kumaravel, K. S. (International Journal of Contemporary Pediatrics, 2017)
Background: Rickettsial diseases including Scrub Typhus are emerging as an important cause of acute undifferentiated febrile illness throughout the Asia-Pacific region. The objectives of the study are to study the clinical profile, complications and outcome of Scrub Typhus cases admitted in rural medical college. Methods: This prospective descriptive study was done at Government Dharmapuri Medical College Hospital, Tamilnadu, between Jul’2015 and Jan’2016. The children who were positive for Scrub Typhus by IgM Elisa were analyzed. Results: During the study period, 151 children (40% of fever cases) were positive for Scrub Typhus. All the children were presented with fever. High-grade fever, chills, vomiting, cough, head ache, were seen in 83%, 41%, 57%, 56% and 32% respectively. 54% of children had lethargy and 10% children brought with convulsions to hospital. Eschar was seen in 68% of children. Lymphadenopathy (70%) and hepatosplenomegaly (more than 56%) were common findings. Shock, respiratory distress, pleural effusion and ascites were seen in 46%, 36%, 40% and 37% respectively. Anemia (74%) and thrombocytopenia (81%) were common lab findings. Shock (46%), ARDS (12%), Meningoencephalitis (10%) and MODS (1.3%) were complications reported. Doxycycline (53%), Azithromycin (11%) and both drugs (36%) were used. Along with fluids, Dopamine (38%), nor-adrenaline (12%), Oxygen through Jackson-Rees Circuit (28%), Non-invasive ventilation (9%) was needed to treat the complications. Conclusions: When a child presents with acute febrile illness, hepatospleenomegaly, lymphadenopathy, anemia with thrombocytopenia and features suggestive of capilary leak diagnosis of Scrub Typhus must be considered. Doxycycline or Azithromycin, proper fluid boluses, Inotropes and O2 through Jackson-Rees Circuit are life saving for scrub typhus and its complications.